Effect of Ramadan Fasting on DNA Repair, Immune System, Inflammation and Cognitive Function in Chronic Kidney Disease Patients: A Systematic Literature Review - Drajad Priyono; Harnavi Harun; Deka Viotra; Zaki Mahmudi Dasril (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: There have been many studies that say Ramadan fasting has a positive effect on reducing BMI, blood sugar, inflammatory factors, and DNA Repair. However, there are still no guidelines for fasting in patients with chronic kidney disease (CKD) both nationally and internationally. This study aimed to conduct a review to explore the effects of Ramadan fasting against chronic kidney disease, specifically on DNA repair, Immune System, Inflammation, and Cognitive Function in patients with chronic kidney disease. Methods: This study is a systematic literature review (SLR) with sources obtained from various reputable journal databases such as PubMed, Cochrane Library, EBSCO, and Elsevier using relevant keywords. The selected articles have passed the inclusion and exclusion criteria. A total of 39 articles that discuss fasting were obtained from Ramadan in chronic kidney disease patients on metabolic response and inflammatory markers in the body. Results: Ramadan fasting has a positive effect on the response to anti-inflammatory, expression of protective genes, markers of kidney and liver function, protective proteome, and oxidative stress. Conclusion: Ramadan fasting may provide a short-term protective effect against levels of systemic inflammation.